2010
DOI: 10.1016/j.jcrs.2009.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of central corneal thickness in normal, keratoconus, and post-laser in situ keratomileusis eyes using Scheimpflug imaging, spectral domain optical coherence tomography, and ultrasound pachymetry

Abstract: There was a statistically significant difference between Scheimpflug imaging and US pachymetry and AS-OCT, with US pachymetry measurements being consistently thicker. Thus, CCT should be interpreted in the context of the instrument used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
55
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 39 publications
4
55
3
2
Order By: Relevance
“…The mean difference between Fourier-domain AS-OCT and highresolution Scheimpflug imaging was generally higher with a wider LoA in the keratoconus group than in the normal group. Grewal et al 34 also compared CCT measurements of an OCT system and a Scheimpflug device in healthy eyes and keratoconic eyes and detected a much lower difference between the 2 tomographers (healthy: 1.5 mm; keratoconus: 2.2 mm) with narrower LoA (healthy: À16.32 to 13.34 mm; keratoconus: À19.08 to 23.53 mm) than we found. However, a recent study using the prototype of swept-light source AS-OCT and a Scheimpflug imaging instrument 40 found a higher difference in central pachymetry values (À42.83 G 30.9 mm with a 95% LoA of À103.40 to 17.73 mm) and a lower difference in ACD measurements (À0.03 G 0.17 mm with a 95% LoA of À0.35 to 0.31 mm) in healthy corneas than those observed in our study.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The mean difference between Fourier-domain AS-OCT and highresolution Scheimpflug imaging was generally higher with a wider LoA in the keratoconus group than in the normal group. Grewal et al 34 also compared CCT measurements of an OCT system and a Scheimpflug device in healthy eyes and keratoconic eyes and detected a much lower difference between the 2 tomographers (healthy: 1.5 mm; keratoconus: 2.2 mm) with narrower LoA (healthy: À16.32 to 13.34 mm; keratoconus: À19.08 to 23.53 mm) than we found. However, a recent study using the prototype of swept-light source AS-OCT and a Scheimpflug imaging instrument 40 found a higher difference in central pachymetry values (À42.83 G 30.9 mm with a 95% LoA of À103.40 to 17.73 mm) and a lower difference in ACD measurements (À0.03 G 0.17 mm with a 95% LoA of À0.35 to 0.31 mm) in healthy corneas than those observed in our study.…”
Section: Discussionsupporting
confidence: 45%
“…This finding is consistent with results reported in the literature. 5,12,[32][33][34][35] In both groups, the difference in the 3 consecutive posterior steep K, posterior flat K, astigmatism, and apical corneal thickness measurements in the same individual was less with AS-OCT than with Scheimpflug imaging. Li et al 36 compared automatic and manual central pachymetry measurements of an anterior segment OCT system (Visante) and a slitlamp OCT system in healthy corneas.…”
Section: Discussionmentioning
confidence: 91%
“…[35][36][37][38] Furthermore, in keratoconic corneas, Pentacam central corneal thickness measurements were found to be more reproducible and repeatable than measurements with ultrasound pachymetry. 39 However, the decrease in pachymetry found in this study could be an artifact of inaccurate measurement by the Pentacam system as a result of the postoperative corneal haze, 39,40 typically seen clinically after CXL. 4,5,9,13,28 Indeed, difficulty measuring post-CXL pachymetry has been reported using the Orbscan scanning-slit topography device (Bausch & Lomb).…”
Section: Discussionmentioning
confidence: 71%
“…In addition, they were not performed in glaucomatous eyes, but in healthy eyes. [12][13][14][15][16] The purpose of this study was to assess the CCT measurements acquired by both devices in patients with POAG. We also speculated the possible effect of glaucomatous drugs in the comparison made between USP and FD-OCT. After an extensive search in PubMed, we concluded that this is the first study of its kind to be performed.…”
mentioning
confidence: 99%